Pelatihan dan Pendapingan jurusan Otomatisasi Tata Kelola Perkantoran (OTKP) SMK Bina Cipta Palembang - Fatmariani, Fatmariani; Alfasyah, Reza (Jurnal Pemberdayaan Umat, 2022)
Purpose: From this community service activity is to increase the application of science and technology in the SMK Bina Cipta Community, especially the Office Governance Authority (OTKP) department using Microsoft Office and Publisher applications. Method: One of the methods used for this PKM activity is training and mentoring. Media used office applications (Ms Office and Publisher), typing manuscripts, making correspondence, making tables, graphs, using formulas and making brochures. This office application application is also used to facilitate work in office administration related to information and aminstaration. The method of service activities is carried out using teaching media and the practice of using Office Applications, namely Ms. Office and Publisher. Results: Students understand how it works and its benefits, understand how to work with office applications, by applying training and mentoring, understanding various types of needs and how they work, recognizing features / menus in office applications, utilizing applications in office administration activities, understanding how to type scripts well, making easy tables, presenting reports, making brochures quickly and neatly,  file (saving, importing, printing). Conclusion: Based on the results of the questionnaire graph that participants are in the interval of 65-78%, it means that this service activity has a positive impact on increasing the application of science and technology to students.